Belarusian scientist Nikolay Kasperovich about Formation of the Latvian national art - Lisov, Alexander (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2014)
In summer of 1927 the Belarusian philologist, historian and ethnographer Nikolay Ivanovich Kasperovich (1900-1937) effectuated a mission to Finland, Estonia, Latvia and Lithuania to study local history practices and pedagogical experience of neighboring countries. At that time he held the post of Academic Secretary of the Central Bureau of Regional Studies at the Belarusian Academy of Sciences. This trip to Finland and to Baltic states lasted from June 28 to September 10, 1927. In Latvia N. I. Kasperovich stayed in Riga and Daugavpils. Several of his publications are dedicated to Latvian literature and to prose and poetry of the Belarusian-speaking writers from Latvia. Special article was written by him about fine art in Latvia, Lithuania and Estonia, it was published in 1928. Evaluations given there by N. I. Kasperovich are very noticeable in the context of his understanding of the problems of formation of national art, comprehension of the content of this concept, understanding of similarities and differences of the formation of national schools of art in Latvia and in Belarus. Here we also can see important parallels with art of Estonia and Lithuania. This article attempts to analyze the views of N. I. Kasperovich on the problem of forming of national art school in Latvia. Through this it is possible to consider ideas of the scientist about formation of national art in Estonia, Lithuania and Belarus. A trip to young Baltic states neighboring Belarusian SSR, a study of their cultural experience created the prerequisites for comparative analysis.